DETERMINAN YANG MEMPENGARUHI AUDIT DELAY PADA MASA PANDEMI COVID 19 - Nia Tresnawaty (Jurnal Liabilitas, 2022)
This research was conducted with the aim of knowing the determinants of audit delay for the manufacturing industry on the IDX. The research was conducted by researchers using causal, there are 166 manufacturing industries on the Indonesia Stock Exchange in 2019-2021. The procedure in determining the sample used is to use criteria and data that are suitable for testing 146 companies with a sample of 438. The type of data is secondary data, the variables studied consist of Company Age, KAP Reputation and Auditor Opinion which are independent variables, while Audit delay is a variable. dependent. The method used in this research is logistic regression. This research shows that the firm age and KAP size variables do not affect audit delay, while auditor's opinion affects audit delay.